Revision of the Scytinopteridae (Hemiptera: Cicadomorpha: Scytinopteroidea) of the Queensland Triassic - Lambkin, Kevin J. (Zootaxa, 2016)
The extinct hemipteran family Scytinopteridae, the presumed ancestors of the Heteroptera, was a small but widely distributed element of the Triassic insect fauna of Queensland. A total of 28 tegmina have been collected at six sites (Gayndah, Esk, Mount Crosby, Riverview, Denmark Hill and Dinmore) in five Middle or Late Triassic Formations. The specimens are remarkably uniform in both wing shape and basic venation, and the generally weakly developed venation of the apical area of the tegmen is rarely clearly preserved. Some consistent variations in tegmen size and in minor venational characters, however, have enabled the identification of six and possibly seven species in three genera, acknowledging of course, the somewhat artificial nature of fossil insect species based solely on isolated wings. Mesoscytina Tillyard, 1919 (= Triassoscarta Tillyard, 1919, syn. nov.), comprising Mesoscytina australis Tillyard, 1919 (= Mesoscytina affinis Tillyard, 1919, syn. nov., = Triassoscarta subcostalis Tillyard, 1919, syn. nov.) (Denmark Hill, Esk), Mesoscytina fistulae sp. nov. (Mount Crosby, Gayndah), Mesoscytina woodsi sp. nov. (Gayndah), and Mesoscytina magna sp. nov. (Dinmore), is distinguished by the combination of the R more or less straight distally and M with three apical branches. The monotypic Eurymelidium Tillyard, 1919, with type species Eurymelidium australe Tillyard, 1919 (Denmark Hill, Dinmore), has R sinuous and M with two apical branches, and the monotypic Apheloscyta Tillyard, 1922, with type species Apheloscyta mesocampta Tillyard, 1922 (Denmark Hill, Riverview) has R more or less straight and M with two apical branches. Three poorly preserved and thus unidentifiable scytinopterid tegmina from Esk, similar in size to Mesoscytina fistulae, are designated as Esk species A.